Analysis of Rejection of Trademark Registration Due to Substantial Similarities in Trademarks : (Case Study of the Mark "de Ratu") - Fitria, Reni; Irianto, Kartika Dewi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Trademark registration is a crucial step for businesses to protect the identity and reputation of their products. However, this registration is often rejected by the competent authority because of the basic similarities with a previously registered mark. This research aims to analyze rejection of trademark registration in Indonesia which is caused by basic similarities. In the context of brand law, principal similarity refers to a situation where two marks are deemed to have similarities that are significant enough to confuse consumers. Based on data from the Directorate General of Intellectual Property (hereinafter referred to as DJKI), the number of trademark registrations rejected for this reason continues to increase every year. This research will discuss the factors that influence rejection of trademark registration, its impact on brand owners, as well as best practices that can be taken to reduce the risk of rejection. With a normative approach, this research will examine existing regulations and how they are implemented in the field